Trade liberalization and wage inequality: new insights from a dynamic trade model with heterogeneous firms and comparative advantage - Wolfgang Lechthaler; Mariya Mileva (Review of World Economics, 2019)
We develop a dynamic general equilibrium trade model with comparative advantage, heterogeneous firms, heterogeneous workers and endogenous firm entry to study wage inequality during the adjustment after trade liberalization and potential policy responses to reduce wage inequality. In the short run, inter-sectoral wage inequality is high but then recedes as more and more workers move to the expanding exporting sector. The skill premium does not change much in the short run but increases substantially in the medium and long run. Training subsidies are more powerful than sector-migration subsidies in reducing the wage inequality induced by trade liberalization.
Keywords: E24; F11; F16; J62; 330; trade liberalization; wage inequality; adjustment dynamics